(untitled) (Research, Society and Development, 2020)
There are countless fruits of the cerrado with economic potential for the development of products that meet consumer demand, such as dietary and functional preserves. However, studies on the characteristics of these products and stability during storage are scarce. Thus, the objective of this study was to evaluate the effect of time and temperature on the physical characteristics of dietetic functional mixed cerrado fruit preserves. For this, mixed preserves were made using marolo, passion fruit and soursop and fructooligosaccharide without added sugar. The preserves were stored at 2 temperatures (25 °c and 35 °c) for 180 days. Analysis of water activity, color and texture profile were performed and the results obtained were evaluated by means of regression analysis. The dietetic functional mixed cerrado fruit preserves were influenced by both time and storage temperature, and the temperature of 35 °c was the variable that most affected physical characteristics. Therefore, in storage at 25 °c, the physical properties of dietetic functional mixed cerrado fruit preserves were more stable.